Association between metabolic dysfunction-associated steatotic liver disease and risk of colorectal cancer or colorectal adenoma: an updated meta-analysis of cohort studies - Zhao, Jian-Feng; Zhou, Ben-Gang; Lv, Yang; Teng, Qiu-Ping; Wang, Xi-Mei; Li, Xiao-Yi; Ding, Yi (Frontiers in Oncology, 2024)
In recent years, the relationship between metabolic dysfunction-associated steatotic liver disease (MASLD) and colorectal cancer (CRC) or colorectal adenoma (CRA) has gained widespread attention. Previous meta-analyses on this subject either incorporated numerous cross-sectional studies, which were susceptible to bias, or concentrated solely on a restricted number of cohort studies. Moreover, with the release of a substantial number of high-quality cohort studies on this subject in the past two years, the findings continue to be debated and contradictory.Therefore, we conducted an updated systematic review and meta-analysis of cohort studies to quantitatively evaluate the magnitude of the association between them.Comprehensive searches of PubMed, Web of Science, and Embase were conducted without language restrictions from the time of their creation up to December, 2023. The pooled hazard ratios (HRs) with 95% confidence interval (CIs) were calculated by the generic inverse variance based on the random-effects model. Moreover, subgroup and sensitivity analyses were performed.Results: A total of 15 cohort studies were analyzed in this meta-analysis, which included 9,958,412 participants. The meta-analysis of 13 cohort studies showed that MASLD was linked to a higher risk of CRC (HR=1.25, 95% CI:1.15-1.36, P < 0.00001). Additionally, further subgroup analysis indicated that the combined HR remained consistent regardless of the study location, nomenclature of fatty liver disease (FLD), confirmation methods for FLD, sample size, follow-up time, and study quality. Furthermore, the meta-analysis of four cohort studies demonstrated that MASLD was correlated with an increased risk of CRA (HR=1.38, 95% CI: 1.17-1.64, P = 0.0002). The sensitivity analysis results further validated the robustness of the aboved findings.The results of our meta-analysis indicated that MASLD was associated with an increased risk of incident CRC/CRA. In the future, it is necessary to conduct more prospective cohort studies to thoroughly assess potential confounding factors, particularly in individuals from Europe and North America. Furthermore, related mechanism studies should be conducted to enhance our understanding of the link between MASLD and CRC/CRA. Systematic review Registration: Open Science Framework registries (https://osf.io/m3p9k).